Quantifying the risk of undetected HIV, hepatitis B virus, or hepatitis C virus infection in Public Health Service increased risk donors. Issue 9 (10th May 2019) - Jones, Jefferson M.; Gurbaxani, Brian M.; Asher, Alice; Sansom, Stephanie; Annambhotla, Pallavi; Moorman, Anne C.; Kamili, Saleem; Brooks, John T.; Basavaraju, Sridhar V.
Abstract : To reduce the risk of HIV, hepatitis B virus (HBV), and hepatitis C virus (HCV) transmission through organ transplantation, donors are universally screened for these infections by nucleic acid tests (NAT). Deceased organ donors are classified as "increased risk" if they engaged in specific behaviors during the 12 months before death. We developed a model to estimate the risk of undetected infection for HIV, HBV, and HCV among NAT‐negative donors specific to the type and timing of donors' potential risk behavior to guide revisions to the 12‐month timeline. Model parameters were estimated, including risk of disease acquisition for increased risk groups, number of virions that multiply to establish infection, virus doubling time, and limit of detection by NAT. Monte Carlo simulation was performed. The risk of undetected infection was <1/1 000 000 for HIV after 14 days, for HBV after 35 days, and for HCV after 7 days from the time of most recent potential exposure to the day of a negative NAT. The period during which reported donor risk behaviors result in an "increased risk" designation can be safely shortened. Abstract : A model to estimate the risk of undetected HIV, hepatitis B and hepatitis C infections among NAT‐negative donors with risk behaviors demonstrates that the 12‐month timeline during which reported donor risk behaviors result in an increased risk donor designation can be safely shortened. Companion articles are onpages 2560 and2570 .